The Guarguaraz Complex and the Neoproterozoic-Cambrian evolution of southwestern Gondwana: Geochemical signatures and geochronological constraints - López de Azarevich, Vanina L. (2009)
The Guarguaraz Complex, in western Argentina, comprises a metasedimentary assemblage, associated with mafic sills and ultramafic bodies intruded by basaltic dikes, which are interpreted as Ordovician dismembered ophiolites. Two kinds of dikes are recognized, a group associated with the metasediments and the other ophiolite-related. Both have N-MORB signatures, with εNd between +3.5 and +8.2, indicating a depleted source, and Grenville model ages between 0.99 and 1.62 Ga. A whole-rock Sm-Nd isochron yielded an age of 655 ± 76 Ma for these mafic rocks, which is compatible with cianobacteria and acritarchae recognized in the clastic metasedimentary platform sequences, that indicate a Neoproterozoic (Vendian)-Cambrian age of deposition. The Guarguaraz metasedimentary-ophiolitic complex represents, therefore, a remnant of an oceanic basin developed to the west of the Grenville-aged Cuyania terrane during the Neoproterozoic. The southernmost extension of these metasedimentary sequences in Cordón del Portillo might represent part of this platform and not fragments of the Chilenia terrane. An extensional event related to the fragmentation of Rodinia is represented by the mafic and ultramafic rocks. The Devonian docking of Chilenia emplaced remnants of ocean floor and slices of the Cuyania terrane (Las Yaretas Gneisses) in tectonic contact with the Neoproterozoic metasediments, marking the Devonian western border of Gondwana. © 2009 Elsevier Ltd. All rights reserved.